KEPALA SEKOLAH SEBAGAI PENDIDIK DAN PENGAWAS DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU - Nellitawati Nellitawati; Aswardi Aswardi; Arwildayanto Arwildayanto (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2019)
Abstract: Indonesian education is being talked about the competence of teachers, in relation to the principal role in improving the teachers pedagogical aspect. The main aim of this study was to determine the education and supervision role of principal in enhancing the pedagogic aspect of teachers in the Vocational School in the Padang City, West Sumatera, Indonesia. Concurrent embedded mixed method research design was provided as a guidance in the process to gain the research objectives. This study delivers questionnaires and interviews to collect data. 261 teachers were involved as respondents to answer a questionnaire that was distributed, and 12 respondents were taken part in interviews. Quantitative data were analyzed using Statistical Package for the Social Sciences while qualitative data were analyzed using thematic analysis. The findings show that the principal role in enhancing the competence of teachers is still at a moderate level, and the pedagogic aspect of teachers at SMK Padang is still at a moderate level. This study also specified that education role of principal were significant influenced the teacher pedagogic. Further, the role of principal supervision was also significant in improving the pedagogical aspect of teachers. Abstrak: Pendidikan Indonesia sedang membicarakan kompetensi guru, kaitannya dengan peran kepala sekolah dalam meningkatkan aspek pedagogis guru. Tujuan utama dari penelitian ini adalah untuk menentukan peran kepala sekolah sebagai pendidik dan pengawas dalam meningkatkan aspek pedagogik guru di Sekolah Kejuruan di Kota Padang, Sumatera Barat, Indonesia. Desain penelitian menggunakan metode campuran dilakukan berdasarkan pedoman dalam mencapai tujuan penelitian. Pengumpulan data menggunakan kuesioner dan wawancara pada 261 orang guru, sedangkan informan untuk menjawab pertanyaan dalam wawancara dilakukan pada 12 orang guru. Data kuantitatif dianalisis menggunakan Paket Statistik Ilmu Sosial sedangkan data kualitatif dianalisis menggunakan analisis tematik. Temuan penelitian menunjukkan bahwa peran kepala sekolah sebagai pendidik dan pengawas dalam meningkatkan kompetensi guru masih berada pada tingkat sedang, dan aspek pedagogik guru di SMK Padang masih berada pada tingkat sedang. Penelitian ini juga menetapkan bahwa peran kepala sekolah sebagai pendidik dan pengawas secara signifikan mempengaruhi kompetensi pedagogik guru.